Breast cancer versus hormone therapy of the menopausal period - Pertyński, Tomasz; Stachowiak, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2005)
In this article some data on the connection between sex steroids and mammary gland development, mitosis, apoptosis as well as cancerogenesis in the mamma have been presented. Also the newest information about the safety of hormone therapy in the group of breast cancer survivors has been quoted. Being of opinion that at present only estrogens are able to treat climacteric symptoms completely, the authors are sharing their opinion about an important role to be played in menopause by the well-tailored, low-dose (25 mg and 37,5 μg 17β-E 2 /day), transdermal estrogen therapy.